The Effect of Motor Parameters on the Induction Motor Speed Sensorless Control System using Luenberger Observer - Bernadeta Wuri Harini (Universitas Sanata Dharma, 2022)
The sensorless control system is a control system without a controlled variable sensor. The controlled variable is estimated using an observer. In this investigation, the sensorless control system is used to control induction motor speed. The observer that is used is the Luenberger observer. One of the drawbacks of the sensorless control system is precision motor parameter values. In this research, the effect of induction motor parameters in a speed sensorless control system, i.e. resistance and inductance motor, will be investigated. The differences in induction motor parameters between the controller and the actual value affect the system response. The value differences of Rr and Rs that can be applied are a maximum of 50%. However, the small differences in the inductance value greatly affect the system response. To get a good response, the value differences of Ls and Lr are between -5% to +5%, while the difference in the value of Lm is between -3% to +3%.